Penerapan Manajemen Finansial Mandiri Melalui Optimalisasi Rebranding Lembaga Dan Filantropi Islam Di Pesantren - Khuliyati (EDUSIANA Jurnal Manajemen dan Pendidikan Islam, 2026)
This study aims to analyze the implementation of independent financial management with in Islamic boarding schools by optimizing institutional rebranding strategies and Islamic philanthropy governance. Financial dependence on external parties often hinders Islamic boarding schools from sustaining their educational and civilizational programs. Therefore, this study explores how integrating a new institutional image (rebranding) with Islamic philanthropy can foster internal fiscal stability. A descriptive qualitative method with a case study approach was employed; data were collected through in depth interviews, observation, and the analysis of financial reports. The results indicate that a strategic synergy between institutional rebranding and the digitalization of Islamic philanthropy significantly enhances the financial independence of Islamic boarding schools. Data analysis revealed the following outcomes: increased fund accumulation a 25% rise in philanthropic revenue over two years; diversified funding sources reduced reliance on student tuition fees to below 20%, offset by surpluses from productive waqf management and business units leveraging the institution's new image; and efficient allocation a fiscal independence ratio showing that 30% of routine operational costs are covered by endowment funds and profits from independent philanthropic activities). This study offers both theoretical and practical contributions toward achieving sustainable financial independence for Islamic boarding schools. It further underscores that Islamic boarding schools Azzahro Pasuruan financial systems no longer rely on conventional schemes but rather on an ecosystem of public accountability driven by institutional reputation (brand equity) and donor trust. Keywords: Independent Financial Management, Institutional Rebranding, Islamic Philanthropy, Islamic boarding schools Independence.